Grassroots relational approaches to agricultural transformation in Latin America - Karen E. Allen; Stefan Ortiz-Przychodzka; Marcondes G. Coelho-Junior; Thora Herrmann; Maggie Atchley; Felipe Benra; Vanessa Chavez; Eduardo Darvin; Julia McCabe; Laura Nahuelhual; Camila Horiye Rodrigues; Barbara Muraca (Ecosystems and People)
Recent emphasis on market-based mechanisms as the key to solving sustainability challenges has left scholars and activists wringing their hands. This frustration and sense of urgency has been particularly poignant in the issues surrounding food production and land-use change. While creative approaches to promoting sustainable land-uses have abounded, intensive agricultural systems persist as a major cause of biodiversity loss. Mounting evidence indicates that a business-as-usual approach to encouraging sustainable food production rests on erroneous assumptions about human value systems and their link to food and land, often resulting in perverse and/or inadequate outcomes. The relational turn arrives onto this scene, revisiting central questions about how values inform action and how policy can leverage values for more sustainable and equitable solutions. We contribute to this discussion through sharing case studies of grassroots sustainable agricultural movements in Latin America. In each, we explore how relational values are linked to transformative action, and how this intersects with or challenges relevant institutions and political structures. Through this analysis, we illustrate the presence of the relational turn within these movements, while questioning whether existing institutions are prepared to embrace a relational approach to policy and norms. Instead, we suggest that the relational turn calls for a more radical transformation of existing institutions than that embraced by most policy makers, and that this central challenge will persist in any attempt to scale up sustainable ‘local’ movements to affect global change.